Christian Elements and Their Folk Adaptations in the Funeral and Memorial Rites of the Ludian Karelians - Minvaleev, Sergei Andreevich (Estonian Literary Museum, the Estonian National Museum and the University of Tartu, 2024)
The articlefocuses on an analysis of the funeral and memorial rituals of the Ludian Karelians in the context of folk religion. For many years, rites of Orthodox origin were either viewed unilaterally or ignored altogether in ethnographic literature, with the reconstruction of ‘pagan’ elements being highlighted, which in turn gave rise to the theory of dual faith. According to the results of my research, the funeral and memorial traditions of the Ludians (from the late 19th to the late 20th century) are based on an Orthodox funeral system in which many aspects derived from a Christian basis found new interpretation. For example, the requirement to light candles was explained as lighting the way to the afterlife, the importance of making confession was so that the dying person’s sins would not attach to the living, and funeral services were to help the soul of the deceased ‘settle’, etc. The principal exponents of the funeral rituals, who ensured the successful transition of the soul to the next world, were representatives of the people: women who washed the body of the deceased, and lamenters, but the church priesthood nonetheless played a significant role in conducting the rituals. The priest’s participation is apparent at all stages of the funeral ritual, from confession to commemoration. Following the abolition of the institution of the church during the Soviet period, the functions of the priest were assumed by elderly women who knew the prayers and church burial traditions.